Barreiras para administração oportuna de antimicrobianos: visão da Enfermagem - Couto, Daniela Sanches (Universidade Federal de São Carlos, 2021)
Introduction: The nursing team is related to the process of antimicrobial administration and it is an important part of ensuring its timely use, that is, correct dose, route and times. Objective: To identify occurrences, which according to nursing professionals, may interfere with the process of timely administration of antimicrobials. Method: This is a survey study with a quantitative approach, with participants being located by the "snowball" technique. Data were collected by self-administered questionnaire via Google Forms®, in August and September 2020, with the participation of 158 professionals, 69% nurses and 31% nursing assistants/technicians. Data were analyzed by descriptive statistics, absolute and relative frequencies, and associations using the Generalized additive models for location, scale, and shape (GAMLSS) model. Results: there was a predominance of female participants (80%), with an average age of 35.25 years, from the southeastern region (64%) and workers in a General Hospital (58%); 59% of nurses and 49% of nursing assistants / technicians declared that they had not participated in training or specific guidance on the preparation and administration of antimicrobials. They pointed out as nursing competencies in the Antimicrobial Stewardship Programs, the control of schedules, dilutions and appropriate intervals for the preparation and administration of antimicrobials; the use of basic precautions and early implementation of contact precautions, monitoring after antimicrobial administration and the insertion of nurses in therapeutic decision-making. As barriers to the antimicrobial administration process, the delay in administration due to obstruction of the pathway, professional overload and the delay in dispensing are opportune. The professional category showed no association with the distribution of total points in the knowledge questionnaire (GAMLSS). Conclusions: it was identified that nursing recognizes situations that may compromise the timely administration of antimicrobials; has little access to courses and training on the subject and little proximity to the Antimicrobial Stewardship Programs, although they already perform isolated actions that contemplate the program's strategy. It is believed that deepening the training of professionals in the subject is fundamental to encourage the full exercise of their role
Barriers to the timely administration of antimicrobials: Nursing vision
Keywords: Antimicrobianos; Programa de gestão de antimicrobianos; Enfermagem; Antimicrobials; Antimicrobial stewardship; Nursing; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE DOENCAS CONTAGIOSAS